THE INTERPLAY OF ESG, ENTERPRISE RISK MANAGEMENT AND CORPORATE REPUTATION IN ENHANCING FIRM VALUE: A SYSTEMATIC LITERATURE REVIEW - Disya Yuke Farhana; Sri Rahayu; Wirmie Eka Putra (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study conducts a systematic literature review of 37 articles to analyze the influence of Environmental, Social, and Governance (ESG) and Enterprise Risk Management (ERM) on firm value, with corporate reputation as a mediating variable. Using Stakeholder Theory and Signalling Theory frameworks, this systematic review identifies that good ESG practices enhance corporate reputation through stakeholder expectation fulfillment and positive market signals. Similarly, effective ERM implementation strengthens reputation through transparent risk management and demonstrates management quality. Corporate reputation serves as a strategic asset mediating the relationship between ESG and ERM with firm value, enhancing trust and market valuation. The integration of ESG and ERM with strengthened reputation becomes the key to creating sustainable firm value. The research recommends consistent implementation of ESG and ERM with transparent disclosure, as well as further exploration of the interaction between both variables across various industry sectors.